Voice and speech for musical theatre : a practical guide - Palmer, Chris (Voice teacher) (Performance books., 2020)
Voice and Speech for Musical Theatre is the first book to combine traditional actor vocal training with musical theatre training, offering support and guidance for performers seeking to train their spoken voice specifically for singing and performing in musical theatre. Performers in musical theatre are working harder than ever. The shifting and extreme nature of the modern musical theatre repertoire requires performers capable of mastering musicianship, singing and dancing while at the same time providing convincing and clear performances as actors. Voice and Speech for Musical Theatre will help train musical theatre performers in the longer modes of voice needed to create convincing and moving performances. Ideal for the triple-threat performer, Voice and Speech for Musical Theatre features exercises for performers, tips for teachers and online video resources, allowing for a focused and outcome-oriented training of vocal techniques for musical theatre performers.